Penalizing strategic preference manipulation in multi-agent decision making. - Yager, R.R (IEEE Transactions on fuzzy systems)
We consider the problem of group decision making where the selection process is based upon a group preference function, obtained by an aggregation of the participating agents individual preference functions. We describe some methods for formulating the group preference from the individual preference functions. We note the possibility of the individual agents strategically manipulating the information they provide, so as to further their own goal of getting their most preferred alternative selected by the group. With this in mind, we suggest ways of modifying the formulation of the group decision functions to discourage strategic manipulation by the participating agents